A perfect moment during imperfect times: Arctic energy research in a low-carbon era. (June 2016) - Sidortsov, Roman
Abstract: In the last decade, Arctic energy research has been dominated by a focus on oil and gas exploration, development, and extraction. This is introductory article to an Energy Research & Social Science special issue, entitled "Arctic Energy: Views from the Social Sciences, " challenges this approach and offers a broader and more inclusive perspective on Arctic energy research. In reflecting this perspective, some of the articles investigate social, economic, political, and environmental aspects of oil and gas development in the region while offering critiques of such development's processes and initiatives, both of which are usually seen in a positive light. Other articles target non-fossil sources and types of energy, thereby providing a view of the Arctic as a living laboratory for energy services. The special issue's broad and inclusive perspective is also represented by the diverse disciplinary, professional, and ethnic backgrounds of the contributing authors, as well as the range of conceptual and methodological approaches.